Towards ERP success in SMEs through business process review prior to implementation - Christofi, Maria Dolores; Nunes, Miguel Baptista; Peng, Guochao Alex; Lin, Angela (My University, 2013)
Purpose: ERP systems are not the exclusive concern of large companies anymore. More and more small and medium sized enterprises (SMEs) are now engaging with the implementation and exploitation of this type of system. However, reports of ERP failure are numerous and frequent. Very often, this failure results from technical and implementation problems. But even more frequently, it is due to lack of preparation, by the companies themselves, for the implementation process. The purpose of the study reported in this paper was to identify and explore ways in which SMEs may need to prepare themselves before implementing ERP systems. Design/methodology/approach: The research took a Cypriot SME as a case study and adopted an inductive approach supported by in-depth interviews as the main method of data collection. The qualitative data collected were analysed by using a thematic analysis approach. Subsequently, a rich picture and concept maps were used to represent the findings generated. Findings: The study identified that business deficiencies and problems, which can impact potential ERP adoption and usage in SMEs, can be localised across business processes boundaries, such as sales order processing, stock control, and bill of materials management, etc. These business problems were found to be attributed to a variety of organisational, technical and human-related reasons. Therefore, this study established that in order to implement ERPs successfully, organisations may require changes in people's work practices and understanding of technology, ownership and control of business processes, as well as organisational wide policies. Research limitations/implications: This study contributes to the knowledge of ERP preparation and business process improvement in SMEs. Practical implications: The findings of the paper provide useful insights for both academic and practitioners who are thinking of implementing ERP systems. The paper contributes to the body of literature on issues that SMEs may need to reflect upon before embarking in a costly and resource intensive process of ERP implementation. Originality/value: Business process improvement is traditionally considered as the result of an ERP project phase. This is how the large majority of the academic literature and the totality of marketing information by ERP vendors portray it. In fact, the reality of practice shows a different scenario with frequent reports of failure and inadequate ERP implementation. This paper aims at breaking with this myth, by proposing that ERPs cannot resolve the large variety of deficient business processes and internal problems that may exist in SMEs. Therefore, this study argues that SMEs need to prepare in advance by engaging in business process reviews prior to the ERP implementation that is engaging in a pre-implementation or preparation phase. © Emerald Group Publishing Limited.
Keywords: Business process improvement; Enterprise resource planning; Pre-implementation; Preparation; Small and medium sized enterprises